Infecção Hospitalar na visão de enfermeiros da Santa Casa de Bagé - RS - Marcelo Carneiro; Fábio Lopes Pedro; Diego Codevilla Teixeira (Universidade de Santa Cruz do Sul, 2012)
Hospital Infection(HI) is that acquired after patient admission and thatmanifests during hospitalization or after discharge, whenit can be related to the hospital admission or procedures.The objective was to verify the point of view of the nursesof Santa Casa de Caridade de Bagé regarding hospitalinfections. Methods: This was an exploratory studycarried out with 32 nurses from Santa Casa de Caridadede Bagé. Data were collected using the in-depth interviewtechnique from July to August 2010, where the subjectsanswered questions about the association betweeninfection control and nursing care, in which answerswere submitted to the theme content analysis technique.Results: They were divided into three symbolic categories:definition of HI, nurses' actions regarding HI and thenurses' perception on HI managers. Conclusion: Theevaluation showed that nurses have a good theoreticalbackground on the subject, as they answered thequestions clearly and appropriately.